Teachers and trainers in a changing world: building up competences for inclusive, green and digitalised vocational education and training (VET): synthesis report - (:unkn) unknown (Publications Office of the European Union, 2022)
The need for investment and for a holistic approach to VET teachers’ and trainers’ professional development is at the heart of high-quality and inclusive VET. Building on the findings of Cedefop/ReferNet thematic perspectives for EU Member States, Norway and Iceland, this synthesis report identifies recent trends and policy developments in Europe on the initial and continuous professional development of VET teachers and trainers. The report points to the different types of VET teachers and trainers in Europe; their evolving and complex role in mastering new technologies, supporting the integration of refugees, identifying and supporting learners at risk of early leaving, and understanding changing labour market needs, to empower and equip students with skills for the future. Their qualifications and opportunities for continuous professional development vary across countries but the challenges policy-makers face in supporting them are shared. The report concludes with key messages for designing effective policies in Europe. (Authors abstract ; BIBB-Doku)
Keywords: P 3.2.3 Lehrer; I 2.2 Europa; 370; 330; Bildungspersonal; Lehrer; Kompetenz; Qualifikation; Flüchtling; Arbeitsmarkt; Europa; Vergleich